Pengaruh Big Data, Bisnis Intelijen Dalam Pengambilan Keputusan - Jaenuri, Listy Adelia; Abyan, Afif; Fikri, Adi Wibowo Noor; Fauzi, Achmad; Sari, Abigael Tiffanny Talenta; Raihan, Dyas; Suherman, Nelvina Meira; Hidayat, Radifan (Prisani Cendekia, 2024)
This research explores the influence of big data and business intelligence (BI) in organizational decision-making. Big data, which is a collection of large, complex, and varied data, and BI, as a tool for analyzing business data, have changed the paradigm of business decision-making. Their integration has increased productivity, innovation, and competitive advantage in dynamic markets. Research results show that the use of big data and BI affects the efficiency and effectiveness of decision-making at different levels of an organization. Big data enables in-depth understanding of customers, market trends, and business operations, while BI enables the fusion and transformation of data into useful information for decision-making. The integration of the two enables more informed decisions, optimization of business processes, and better results. Nonetheless, further research is needed to understand their impact in different business context.